2010
DOI: 10.2174/1874288200903010017
|View full text |Cite
|
Sign up to set email alerts
|

Resistant Starches (RS2 and RS3) have Variable Effects on Bone Mineral Status in Rats

Abstract: Nondigestible oligosaccharides may increase mineral absorption by changing the intestinal environment. The effect of feeding a diet containing 5% resistant starch, RS2 (uncooked native) or RS3, (cooked and retrograded) on calcium absorption and bone mineral status was studied in growing male rats for 4 weeks. Almost 100g more feed was consumed with resistant starch compared to control in four weeks. Mineral status improved as determined by femur concentration, but not through absorption. Mineral content of fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
1
8
0
2
Order By: Relevance
“…There are a few reports on the effect of RS on BMD. Zafar et al, reported that diet treated with 5% RS did not increase calcium absorption capacity, and did not affect femoral BMD in male rats, which were fed with the recommended levels of dietary calcium (0.5%) [ 35 ]. Although the dietary calcium level used in the study was the same as our study, the diet treated with AH-HAS (12% RS) attenuated the OVX induced bone loss in our study.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few reports on the effect of RS on BMD. Zafar et al, reported that diet treated with 5% RS did not increase calcium absorption capacity, and did not affect femoral BMD in male rats, which were fed with the recommended levels of dietary calcium (0.5%) [ 35 ]. Although the dietary calcium level used in the study was the same as our study, the diet treated with AH-HAS (12% RS) attenuated the OVX induced bone loss in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were diluted with DW and analyzed by the inductively coupled plasma (ICP‐OES‐7300 DV, Perkin Elmer) using the wavelength of 766, 285, 227, 238, and 206 for K, Mg, Ca, Fe, and Zn, respectively. [ 8 ]…”
Section: Methodsmentioning
confidence: 99%
“…The group percent mineral absorptions of Ca, Mg, K, Fe, and Zn were calculated from ( mineral intake − fecal mineral loss) / mineral intake) × 100. [ 8 ]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations